Evaluation of human discomfort from combined noise and whole-body vibration in passenger vehicle - Aladdin, Mohd Farid; Abdul Jalil, Nawal Aswan; Guan, Ng Yee; Md Rezali, Khairil Anas; Adam, Siti Aisyah (Universiti Malaysia Pahang, 2019)
Exposure to noise and whole-body vibration (WBV) has been a key element in determining comfort levels in transportation systems. In the automotive industry, researchers and engineers continuously work on reducing noise and vibration levels to minimize discomfort. Noise annoyance in vehicles results from structure-borne as well as air-borne noise from vehicle powertrain, tires and aeroacoustics. Whole-body vibration affects vehicle passenger comfort at the seat pan, back rest and feet. The objective of this research is to evaluate the comfort level of seated passengers in a vehicle from noise and whole-body vibration by considering both separate and combined modality. The noise and vibration data were recorded and analysed in two vehicles on the same highway road with four different speeds. The vibration exposure in vehicle were evaluated based on ISO2631-1:1997. Noise exposure was based on A-weighted sound pressure level. The combined discomfort on noise and vibration were quantified. The vibration results identified clear dominant of z-axis vertical vibration on seat pan, backrest and feet in both vehicles. The discomfort of combined noise and vibration showed that vehicle B caused a higher discomfort level at the high vehicle speed of 90 km/h and 110 km/h. The Relative Discomfort Indicator (RDI) were introduced to compare levels of discomfort from noise and vibration in different vehicles with varying speeds. The result suggests that the RDI value for vehicle A relative to vehicle B is negative at higher vehicle speed which further indicates that at higher speed, vehicle B have a higher discomfort level compared to vehicle A. The RDI value is expected to be useful for automotive Noise, vibration and harshness (NVH) improvement.